Passiflora echinasteris: a new species of subgenus Passiflora, series Serratifoliae (Passifloraceae) from the Brazilian Amazon - Koch, Ana Kelly; de Rezende Cardoso, André Luiz; Ilkiu-Borges, Anna Luiza (Phytotaxa, 2015)
Passiflora echinasteris from a secondary vegetation area on the Great Curve of the Xingu River, in the Brazilian Amazon, is newly described. It belongs to the series Serratifoliae with three other Brazilian species. The new species is illustrated and its affinities with related species are discussed, and a key to the Brazilian species of the series is provided.